Contabilidade tributária: análise dos reflexos decisórios da escolha da empresa de pequeno e médio porte pelo regime de tributação: lucro real, lucro presumido e simples nacional - Gazola, Miguel (2013)
This research aims to produce a tax planning that can assist in finding an alternative, within legal aspects, to the best or lowest tax burden. Based on this concept, it is necessary to analyze all existing taxation regimes in Brazil and for a better research conclusion, it will be analyzed three companies with distinct branches and areas. Legal entities, within certain rules, will be able to choose from available taxation forms, ie, Taxable Income, National Income Deemed and Simple. Currently taxes in Brazil are very relevant to legal entities cost and expenses composition, regardless the size the company presents itself. Therefore it is necessary to analyze alternatives that would fit better for a given entity, since each tax regime has particular characteristics, are quite different, and will provide advantages or disadvantages for each company given the system chosen. Thus, by the survey raised in the case study, it will be assessed the best taxation way for each type of activity the company plays, being a selling clothes business, an industrial company that manufactures textile products or a services provider in construction